Institutional work, agonism, and the accounting profession: The case of the Lebanese Association for Certified Public Accountants - Sadaka, Sami Fares (2017)
This thesis explores the development of the accounting profession with a specific reference to the case of Lebanon, utilising a qualitative research design. The establishment of the exclusive body of accounting in Lebanon, the Lebanese Association for Certified Public Accountants (LACPA), in 1994 constitutes a central element of this development. The analysis refers back to the period preceding the LACPA, specifically from when the first union of accountants in Lebanon was established in 1963. While the professionalization project of accounting in Lebanon, which is when the accounting profession was recognised by the state like other reputable professions, along with institutionalising entry requirements, could be understood in terms of several influencing factors, such as the French colonial legacy, or the Civil War and the reconstruction project associated with it, this case argues that this project is the outcome of the work of indigenous accounting practitioners. The data collected in this study is theoretically analysed within the concept institutional work, defined as the purposive action of individuals and organisations aimed at creating, maintaining and disrupting institutions (Lawrence et al., 2009). As institutions are traditionally framed within a structural understanding, the concept of institutional work, while not neglecting the significance of structural factors in relation to institutions, demonstrates that the role of actors and their actions in relation to institutions should not be overlooked. After addressing the establishment of the exclusive body of accounting in Lebanon, this case explores how the accounting profession is being maintained amid political, religious and sectarian divisions, and demonstrates that the survival of this profession is understood beyond the technical aspects of the accounting profession and practice, to embody these broader divisions. Given this multidimensional nature of the maintenance/survival of the accounting profession as an institution, the notion of agonistic pluralism (Mouffe, 2013) provided a more nuanced understanding of the accounting profession as an arena that is composed of different groups, and how these groups' interactions enhance our knowledge and understanding of the accounting profession. This study relies on semi-structured interviews with key players of the accounting profession in Lebanon, mainly executive members of the LACPA, and supports these interviews with archival documents. This approach was chosen because personal experiences and discourses enable a better understanding of actions and intentions of actors, and their inter-relatedness with political and religious/sectarian considerations. This study reveals what takes place in the backstage of governance, how and on what basis the different groups interact with each other, and ultimately how this is reflected on the function of the LACPA as the exclusive body of accounting in Lebanon. This thesis provides an empirical study that enables a re-thinking of the essence of the accounting profession, not only because this context is under-researched, but also because of the following reasons. First, this case addresses how local accounting practitioners, through engaging in strategies of institutional work, were able to grant the accounting profession authority and recognition at a time when the state and politicians were unwilling to legislate for the accounting profession. Second, this case understands the establishment and maintenance of the accounting profession in terms of agonising relations between groups with different perspectives. Thus, an integral part of institutional work is to establish an agonistic environment that would ensure the survival of the accounting profession, amid divided re-constructed identities of actors. Moreover, by addressing the work of actors of a professional association, this case illustrates how the accounting profession and its maintenance are related to other institutions operating at a broader level. This contributes to our knowledge about how professional associations engage in institutional work (Ramirez, 2013) by demonstrating that the aspired agonistic environment encompasses not only professional considerations, but also other political and religious considerations that are vital for the maintenance of the accounting profession. This case sheds light about phenomena, relationships, and divisions that are present nearly in all contexts, yet not explicitly associated with the accounting profession, hence, a broader understanding of the essence of the accounting profession is presented in this thesis.